Erratum for: Halal Products Assurance Policy Model and Its Impact on Sustainability of Fish Ball SMI using System Dynamics Simulation Approach - Handayani, Dwi Iryaning; Haryono, Haryono; Prihatiningsih, Tri (Department of Agro-industrial Technology, University of Brawijaya, 2020)
We apologize for the error in the article